Highlights from the 25th European Congress on Gynaecological Oncology in Barcelona: the ENYGO-IJGC Fellow Interviews - Angeles, Martina Aida; Agusti, Nuria; Bonaldo, Giulio; Bizzarri, Nicolò; Bilir, Esra; Piedimonte, Sabrina; Olearo, Elena; Navarro Santana, Beatriz; Sahin Aker, Seda; El Hajj, Houssein; Ghirardi, Valentina; Kacperczyk-Bartnik, Joanna; et al. (International journal of gynecological cancer, 2024)
In March 2024, 12 European Network of Young Gynae Oncologists-International Journal of Gynaecological Cancer (ENYGO-IJGC) Editorial Fellows conducted 10 interviews with senior opinion leaders on original and controversial topics in the field of gynecologic oncology presented during the 25th European Society of Gynaecological Oncology (ESGO) Congress in Barcelona, Spain. This article provides a summary and overview of the content of these discussions summarizing key points presented at the meeting. These selected interviews were chosen by consensus by the ENYGO-IJGC Editorial Fellows based on novelty and relevance to the field of gynecologic oncology.